Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw dan Talking Stick Terhadap Hasil Belajar Matematika Di SDN Mlajah 2 Bangkalan - Zainal Arifin (Universitas PGRI Adi Buana Surabaya, 2019)
This study in general is to find out the effect of Jigsaw Cooperative Learning Model andTalking Stick on Learning Outcomes of Mlajah 2 Bangkalan public elementary school. Inproving and analyzing this in data collection by giving questionnaires and pretest andpost-test questions. Testing data analysis uses validity, reliability, normality andhomogeneity tests and One Way Anova. The results of the study based on hypothesistesting using the first hypothesis SPSS obtained the value of Sig. of 0.006 <0.05, so it canbe concluded that the type of jigsaw cooperative learning model has a significant effecton mathematics learning outcomes The second hypothesis is based on the results ofhypothesis testing on the Sig values obtained. of 0,000 <0.05, so it can be concluded thatthe learning model of talking sticks in class B also has a significant effect on studentlearning outcomes in mathematics and hypotheses using the third One Way Anova basedon the results of hypothesis testing obtained by the Sig. of 0.029 <0.05, so it can beconcluded that Talking Sticks are better compared to cooperative jigsaw types.